Investigating Life Cycle Cost, Environmental and Social Impacts of a Lithium–Ion Battery Pack - Antonella Accardo; Gaia Gentilucci; Luca Pontone; Ezio Spessa (IEEE Open Journal of Vehicular Technology, 2025)
This study evaluates the environmental, economic, and social impacts of the life cycle of a battery pack for automotive applications. The analysis employs Life Cycle Assessment (LCA) for environmental assessment, Life Cycle Costing (LCC) for economic assessment, and Social Life Cycle Assessment (S-LCA) for social impact analysis. Key locations of non-European raw material extraction and refining are considered for the supply chain. Instead, European countries are considered the final destination for battery pack manufacturing and assembly, use, and End-of-Life (EoL). For the use and EoL phases, three scenarios are analyzed. The LCA results indicate that greenhouse gas emissions vary from 77.2 kg CO $_{2}$ -eq/kWh to 80.7 kg CO $_{2}$ -eq/kWh across the evaluated scenarios. Similarly, the economic assessment estimates LCCs between 77.7 EUR/kWh and 79.4 EUR/kWh, depending on the scenario. The S-LCA results highlight significant risks related to fair pay across numerous countries during the raw material extraction phase, particularly for cobalt (Democratic Republic of the Congo), manganese (South Africa), nickel (Australia), lithium (Australia), and graphite (China). In addition, the score for health and safety concerns presents high risks associated with cobalt, manganese, and nickel mining. In contrast, no significant critical social impacts are found for the use and EoL phases.